Evolution of catastrophic health expenditure in a high income country: incidence versus inequalities - Carlota Quintal (BMC, 2019)
Abstract Background Catastrophic health expenditure (CHE) is well established as an indicator of financial protection on which there is extensive literature. However, most works analyse mainly low to middle income countries and do not address the different distributional dimensions of CHE. We argue that, besides incidence, the latter are crucial to better grasp the scope and nature of financial protection problems. Our objectives are therefore to analyse the evolution of CHE in a high income country, considering both its incidence and distribution. Methods Data are taken from the last three waves of the Portuguese Household Budget Survey conducted in 2005/2006, 2010/2011 and 2015/2016. To identify CHE, the approach adopted is capacity to pay/normative food spending, at the 40% threshold. To analyse distribution, concentration curves and indices (CI) are used and adjusted odds ratios are calculated. Results The incidence of CHE was 2.57, 1.79 and 0.46%, in 2005, 2010 and 2015, respectively. CHE became highly concentrated among the poorest (the respective CI evolved from − 0.390 in 2005 to − 0.758 in 2015) and among families with elderly people (the absolute CI evolved from 0.520 in 2005 to 0.740 in 2015). Absolute CI in geographical context also increased over time (0.354 in 2015, 0.019 in 2005). Medicines represented by far the largest share of catastrophic payments, although, in this case concentration decreased (the median share of medicines diminished from 93 to 43% over the period analysed). Contrarily, the weight of expenses incurred with consultation fees has been growing (even for General Practitioners, despite the NHS coverage of primary care). Conclusions The incidence of CHE and inequality in its distribution might progress in the same direction or not, but most importantly policy makers should pay attention to the distributional dimensions of CHE as these might provide useful insight to target households at risk. Greater concentration of CHE can actually be regarded as an opportunity for policy making, because interventions to tackle CHE become more confined. Monitoring the distribution of payments across services can also contribute to early detection of emerging (and even, unexpected) drivers of catastrophic payments.